The Risks of Unregulated Artificial Intelligence in Indonesia: Challenges and Solutions - Ahmad Zharfan; Ghadamfar Muflih Idroes; Faisal A Rani (Genesis Law and Social Sciences, 2026)
The rapid diffusion of artificial intelligence (AI) systems in Indonesia has outpaced the country's regulatory capacity. Although several statutory and subordinate instruments touch upon AI-related concerns, including Law Number 11 of 2008 on Electronic Information and Transactions as most recently amended by Law Number 1 of 2024, Law Number 27 of 2022 on Personal Data Protection, Government Regulation Number 71 of 2019, the Circular Letter of the Minister of Communication and Informatics Number 9 of 2023 on the Ethics of Artificial Intelligence, the Circular Letter of the Financial Services Authority Number 19/SEOJK.06/2023, and the 2020-2045 National Strategy for Artificial Intelligence, none of these instruments establishes a comprehensive legal regime for AI. Employing normative legal research combining statutory, conceptual, and comparative approaches, this article argues that Indonesia's prevailing reliance on subordinate regulations and ministerial circulars is constitutionally insufficient for a regulatory domain that engages fundamental rights protected by Article 28J(2) of the 1945 Constitution. Drawing comparatively upon the European Union's risk-based AI Act, Singapore's Model AI Governance Framework, and Japan's agile governance approach, the article proposes a primary statute (Undang-Undang) on AI as the constitutionally proper anchor, with subordinate Presidential and Ministerial Regulations performing operational functions. The contribution is not the now familiar claim that Indonesia needs AI regulation, but the reframing of that claim as a question of constitutional form, mapping a civil law hierarchy of instruments onto it and offering Indonesian legislators and ASEAN scholarship a worked architecture suited to a civil law jurisdiction.